ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN PUBLIK DI INDONESIA - Winny Lian Seventeen (Universitas Prof.Hazairin,SH Bengkulu, 2019)
This study aimed to analyze the bankruptcy prediction public companies in Indonesia, The population in this study is a bankrupt company to ever be listed on the Stock Exchange in 1998-2015 and similar companies for comparison. This type of research used in this research is descriptive research with quantitative approach. The samples selected 42 enterprise units of analysis. Tools of data analysis in this study using Altman Z